Propuesta de un manual de procedimiento para mejorar la aplicación de la contratación pública en la EMMAP – EP - Silva Ormaza, María Belén (2024)
This research was carried out at the EMMAP-EP with the objective of proposing a procedural manual for the improvement of public procurement. Within which the inductive, deductive and analytical-synthetic methods were applied, in addition to the interview and survey as data collection. In the results, the research has achieved a detailed and exhaustive analysis of the procedures used by the EMMAP-EP Drinking Water Company in its public contracting processes and specific steps have been identified, such as the detailed identification of needs, the preparation of terms and technical specifications, the selection of suppliers based on clear and objective criteria, the efficient management of contracts and the proactive monitoring of their compliance. Furthermore, transparency at each stage of the process has been emphasized as a fundamental principle, guaranteeing integrity and fairness in public procurement. Regarding the creation of a complete and detailed Manual of Procedures for the Application of Public Procurement in the EMMAP-EP. This is based on best practices and is aligned with the current legal framework in Ecuador. Its content offers a meticulous and clear guide to carry out contracting processes, with the aim of substantially improving transparency, efficiency and equity in said procedures. The preparation of this manual represents a significant advance in the optimization of public procurement management of the EMMAP-EP.